Priority based Hybrid Automation Testing - Priyanka (My University, 2013)
Software testing is an important means to ensure software quality and to improve software reliability. The rapid development in the software industry has raised new demands and challenges for improving the quality of software testing. The software applications once developed need to be maintained as the frequent updates in the software makes them vulnerable without rigorous testing. As the size and complexity of software applications is continually growing, manual testing becomes infeasible. Automation of the software testing process saves time and provides better utilization of resources and thus, plays a significant role in the testing activity. The proposed hybrid approach extends support to automatic testing by providing functionality of both GUI and Code based testing. Moreover, it also prioritizes modules under test to achieve a certain degrees of confidence in the testing of applications that are under tight project deadlines. The proposed approach allows to combine the benefits of both GUI and Code based testing while keeping a simple interface, and by treating the two types of tests in a unified fashion
MT, SMCA
Keywords: Priority; Automation Testing